2022
DOI: 10.3390/ijerph192113781
|View full text |Cite
|
Sign up to set email alerts
|

Tick Infestation in Migratory Birds of the Vistula River Valley, Poland

Abstract: Migratory birds play an important role in the eco-epidemiology of tick-borne diseases due to their ability to carry ticks for long distances. The aim of the present study was to investigate the prevalence and factors influencing the intensity of tick infestation in migratory birds. The study was conducted in a locality situated in the Vistula River valley, eastern Poland, during autumn, when the high migratory activity of birds is registered in the region. The birds were captured using ornithological nets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…The bird species in our study, mostly passerines, showed a remarkable 2.5% tick prevalence, consistent with other studies across Europe, such as the prevalence of 1.7% reported in Greece [39], 3.1% in Germany [40], 4.4% in Poland [41], or 2.0% in Sweden-Denmark [42], but far from the 58.0% reported in a Lyme endemic area in Switzerland [43], 41.1% in Czechia [44], 36.7% in Slovakia and Czechia [45], or 32.4% (Mafra, Lisboa) and 16.7% (Coimbra) reported in two forested areas in western Portugal [46]. A detailed analysis of the epidemiological studies carried out in Europe in the last 30 years (Table S2) revealed great methodological differences between them, both in geographical and climatic characteristics of the studied areas, diversity, and abundance of bird species and other tick host animals, or in the capture period.…”
Section: Discussionsupporting
confidence: 92%
“…The bird species in our study, mostly passerines, showed a remarkable 2.5% tick prevalence, consistent with other studies across Europe, such as the prevalence of 1.7% reported in Greece [39], 3.1% in Germany [40], 4.4% in Poland [41], or 2.0% in Sweden-Denmark [42], but far from the 58.0% reported in a Lyme endemic area in Switzerland [43], 41.1% in Czechia [44], 36.7% in Slovakia and Czechia [45], or 32.4% (Mafra, Lisboa) and 16.7% (Coimbra) reported in two forested areas in western Portugal [46]. A detailed analysis of the epidemiological studies carried out in Europe in the last 30 years (Table S2) revealed great methodological differences between them, both in geographical and climatic characteristics of the studied areas, diversity, and abundance of bird species and other tick host animals, or in the capture period.…”
Section: Discussionsupporting
confidence: 92%
“…low infection costs (Bensch et al 2007; Kleijn et al 2010; Bengtsson et al, 2016, but see (Asghar et al 2011; van Dijk et al 2015). Interestingly, of the three bird studies where there was a pattern of infection with migration, the parasites sampled were either helminths (Vestbo et al, 2019 or arthropods (Sándor et al, 2014; Zając et al, 2022; Table S1). That said, studies on birds most often found no difference in infection intensity between migrants and residents.…”
Section: Resultsmentioning
confidence: 99%
“…At the Kaliszany Ornithological Station, I. trianguliceps were collected from blackcaps Sylvia atricapilla and song thrushes Turdus philomelos (Zajac et al. 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…( 2010 ) 4 l Poland Nowak-Chmura ( 2013 ) 1 l Poland Zajac et al. ( 2022 ) 1 l Romania Coipan et al. ( 2011 ) 3 l Romania Mihalca et al.…”
Section: Discussionmentioning
confidence: 99%